An integrated multi layers approach for detecting unknown malware behaviours - Imad Wajeeh AL-Shahwani, Humam; Mohamed Yassin, Warusia; Zainalabidin, Zaheera; Rasheed, Mohammed (International Journal of Engineering and Technology, 2019)
Malware represents one of the dangerous threats to computer security. Dynamic analysis has difficulties in detecting unknown malware. This paper developed an integrated multi â€“ layer detection approach to provide more accuracy in detecting malware. User interface integrated with Virus Total was designed as a first layer which represented a warning system for malware infection, Malware data base within malware samples as a second layer, Cuckoo as a third layer, Bull guard as a fourth layer and IDA pro as a fifth layer. The results showed that the use of fifth layers was better than the use of a single detector without merging. For example, the efficiency of the proposed approach is 100% compared with 18% and 63% of Virus Total and Bellegarde respectively.Â Â